Informalidad y subempleo: un modelo probit bivariado aplicado al Valle del Cauca - Humberto Ortiz, Carlos; Uribe, José Ignacio; García, Gustavo Adolfo (Sociedad y Economía, 2007)
In this paper informal workers are described vis a vis underemployed workers in Valle del Cauca (Colombia). An integrated analysis of determinants of informality and underemployment that embodies the correlation of error terms (model bivariate probit) is also carried out. This procedure yields a better characterization of the quality of jobs in Valle del Cauca.